Social Demographic Factors in High-Risk Pregnancy: Analysis of Indonesian Health Survey Data 2023 - Suksesty, Catur Erty; Cahyati , Widya Hary; Handayani, Oktia Woro Kasmini (Journal of Creativity Student, 2025)
High-risk pregnancy is a condition that can negatively impact the health of both the mother and the fetus. Social and demographic factors such as maternal age, educational level, economic status, employment, and place of residence contribute to pregnancy risk levels. Indonesia continues to experience a high maternal mortality rate (MMR), necessitating an in-depth analysis of the social determinants affecting high-risk pregnancies. This study employs a cross-sectional design and utilizes secondary data from the 2023 Indonesian Health Survey (SKI). The study sample consists of 46,699 pregnant women from 38 provinces across Indonesia. The independent variables include maternal age, education, employment, economic status, and place of residence, while the dependent variable is high-risk pregnancy. Data analysis was conducted using the chi-square test to identify associations between social determinants and pregnancy risk. The findings indicate that 15.4% of pregnant women experience risk factors in their pregnancy. Significant social factors associated with high-risk pregnancy include maternal age, education level, employment, place of residence, and economic status (p < 0.05). Adolescent mothers (aged 10–19 years) and older mothers (>35 years) are at higher risk. Women with low education levels, unemployment, and lower economic status are also more vulnerable to high-risk pregnancies. High-risk pregnancy is influenced by various social and demographic factors. Therefore, inclusive health policies are needed to improve maternal healthcare access, especially for high-risk groups. Health education programs on reproductive health and increased access to prenatal healthcare services can help reduce the prevalence of high-risk pregnancies in Indonesia.